2020
DOI: 10.1002/jcp.30034
|View full text |Cite
|
Sign up to set email alerts
|

Acute rimonabant treatment promotes protein synthesis in C2C12 myotubes through a CB1‐independent mechanism

Abstract: Sarcopenia is an age‐related loss of muscle mass associated with changes in skeletal muscle protein homeostasis due to lipid accumulation and anabolic resistance; changes that are also commonly described in obesity. Activation of the endocannabinoid system is associated with the development of obesity and insulin resistance, and with the perturbed skeletal muscle development. Taken together this suggests that endocannabinoids could be regulators of skeletal muscle protein homeostasis. Here we report that rimon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 70 publications
1
13
0
Order By: Relevance
“…The treatment of satellite cells with rimonabant increased their differentiation and the number of regenerated myofibres, and prevented the loss of mobility in mdx mice 14 . Last, in a recent study, we demonstrated that acute inhibition of the ECS by rimonabant was able to prevent dexamethasone‐induced atrophy and to stimulate protein synthesis in a model of myotubes in culture 15 …”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…The treatment of satellite cells with rimonabant increased their differentiation and the number of regenerated myofibres, and prevented the loss of mobility in mdx mice 14 . Last, in a recent study, we demonstrated that acute inhibition of the ECS by rimonabant was able to prevent dexamethasone‐induced atrophy and to stimulate protein synthesis in a model of myotubes in culture 15 …”
Section: Introductionmentioning
confidence: 74%
“…14 Last, in a recent study, we demonstrated that acute inhibition of the ECS by rimonabant was able to prevent dexamethasone-induced atrophy and to stimulate protein synthesis in a model of myotubes in culture. 15 Whether sarcopenia is associated with modifications of endocannabinoid tone and alterations of the ECS is, to our knowledge, unknown. Therefore, the aim of the present study was (1) to characterize the changes of the circulating and tissue levels of endocannabinoids in a context of sarcopenia, (2) to characterize the alterations of the ECS genes in the adipose tissue and skeletal muscle, and (3) to analyse whether these alterations can be associated with muscle mass, function, and mobility in old rats.…”
Section: Introductionmentioning
confidence: 96%
“…However, Le Bacquer et al (2022) co-incubated C2C12 myotubes with dexamethasone and rimonabant for 24 h, and the atrophy was prevented in myotubes exposed to rimonabant, without affecting the atrogin-1/MAFbx ratio. The authors also found that rimonabant stimulates protein synthesis and CB1 agonists are unable to modulate protein synthesis, suggesting a CB1-independent mechanism [ 59 ]. In vitro and in vivo models, mouse strains, and rimonabant doses can explain these controversial results.…”
Section: Discussionmentioning
confidence: 99%
“…Pekkala et al found that CB 1 antagonism in human myotubes increased protein synthesis, as well as the expression of the downstream mediators of the anabolic mammalian target of rapamycin complex 1 (mTORC1) pathway (S6K1, S6rp, and 4E‐BP1), which occurred in an ERK1/2‐dependent but, interestingly, mTORC1‐independent way (Pekkala et al, 2015). Accordingly, treatment with the CB 1 antagonist rimonabant prevented dexamethasone‐induced atrophy in C 2 C 12 cells via an increase in protein synthesis and mTOR expression, as well as intracellular Ca 2+ levels (Le Bacquer, Lanchais, et al, 2021). In contrast to Pekkala et al (2015), the increase in protein synthesis was not mediated by CB 1 , indicating that different mechanisms explain the anabolic potential of rimonabant, independent from CB 1 (Le Bacquer, Lanchais, et al, 2021).…”
Section: Cannabinoid System and Muscle Homeostasis: Paths And Challengesmentioning
confidence: 99%
“…Accordingly, treatment with the CB 1 antagonist rimonabant prevented dexamethasone‐induced atrophy in C 2 C 12 cells via an increase in protein synthesis and mTOR expression, as well as intracellular Ca 2+ levels (Le Bacquer, Lanchais, et al, 2021). In contrast to Pekkala et al (2015), the increase in protein synthesis was not mediated by CB 1 , indicating that different mechanisms explain the anabolic potential of rimonabant, independent from CB 1 (Le Bacquer, Lanchais, et al, 2021). It cannot be excluded that other receptors that physically and functionally interact with CB 1 , such as the β2‐adrenoceptor, stimulated protein synthesis upon CB 1 antagonist treatment (Figure 4).…”
Section: Cannabinoid System and Muscle Homeostasis: Paths And Challengesmentioning
confidence: 99%